Diversity, frequency, and geographic distribution of facultative bacterial endosymbionts in introduced aphid pests. (17th May 2016) - Sepúlveda, Daniela A.; Zepeda‐Paulo, Francisca; Ramírez, Claudio C.; Lavandero, Blas; Figueroa, Christian C.
Abstract: Facultative bacterial endosymbionts in insects have been under intense study during the last years. Endosymbionts can modify the insect's phenotype, conferring adaptive advantages under environmental stress. This seems particularly relevant for a group of worldwide agricultural aphid pests, because endosymbionts modify key fitness‐related traits, including host plant use, protection against natural enemies and heat tolerance. Aimed to understand the role of facultative endosymbionts on the success of introduced aphid pests, the distribution and abundance of 5 facultative endosymbionts ( Hamiltonella defensa, Regiella insecticola, Serratia symbiotica, Rickettsia and Spiroplasma ) were studied and compared in 4 cereal aphids ( Sitobion avenae, Diuraphis noxia, Metopolophium dirhodum and Schizaphis graminium ) and in the pea aphid Acyrthosiphon pisum complex from 2 agroclimatic zones in Chile. Overall, infections with facultative endosymbionts exhibited a highly variable and characteristic pattern depending on the aphid species/host race and geographic zone, which could explain the success of aphid pest populations after their introduction. While S. symbiotica and H. defensa were the most frequent endosymbionts carried by the A. pisum pea‐race and A. pisum alfalfa‐race aphids, respectively, the most frequent facultative endosymbiont carried by all cereal aphids was R. insecticola . Interestingly, a highly variable composition of endosymbionts carried by S. avenae was also observed between agroclimatic zones, suggesting that endosymbionts are responding differentially to abiotic variables (temperature and precipitations). In addition, our findings constitute the first report of bacterial endosymbionts in cereal aphid species not screened before, and also the first report of aphid endosymbionts in Chile.